How to measure the ecological compensation threshold in the upper Yangtze River basin, China? An approach for coupling InVEST and grey water footprint - Guan, Dongjie; Wu, Lei; Cheng, Lidan; Zhang, Yuxiang; Zhou, Lilei (Frontiers in Earth Science, 2022)
Defining a reasonable and feasible watershed ecological compensation threshold is the key to protecting watershed ecological functions and maintaining the sustainable utilization of watershed ecosystems. However, many studies have obtained compensation values that are too high to promote the implementation of ecological compensation policies. This study chose the upper reaches of the Yangtze River as the research area, taking water resources closer to people's daily needs as the evaluation object. Based on the InVEST(Integrated Valuation of Ecosystem Services and Trade-offs) model and grey water footprint method, the ecological compensation threshold model for water resources was established. Combined with the eco-compensation priority sequence coefficient identification of protected areas and beneficiary areas and allowed for the measurement of the watershed ecological compensation value in 2015 and 2020. Finally, compare the advantages and disadvantages of different ecological compensation calculation methods, compare the gap between different watershed ecological compensation standards and the theoretical threshold globally. The results showed that from 2015 to 2020, the value of the water content in the upper reaches of the Yangtze River increased, while the value of the grey water footprint decreased. The classified watershed ecological compensation beneficiary areas were mainly concentrated in the central-eastern and southern parts of the upper Yangtze River, while the ecological compensation protected areas were concentrated in the western and northwestern parts. The mean absolute values of the watershed ecological compensation thresholds for each prefecture-level city and state ranged from 0.430 to 24.6326 billion CNY in 2015 and from 0.671 to 41.602 billion CNY in 2020, which were close to the actual values. Among the different land-use types, the water conservation service value per unit area of shrubs was the highest. The lower limit value of watershed ecological compensation calculated using the grey water footprint method was closer to the amount of compensation in practice than was the commonly used opportunity cost method. The findings of the study can help improve the watershed ecological compensation mechanism in the upper Yangtze River region, promote win–win cooperation among transboundary watershed areas, and form a harmonious and stable green development model.